New approaches for non-classically damped system eigenanalysis. - Khanlari, Karen
This paper presents three new approaches for solving eigenvalue problems of non-classically damped linear dynamics systems with fewer calculations than the conventional state vector approach. In the latter
Keywords: Non-classical damped system; Dynamic system; Eigenproblem; Expansion approach; State vector approach